Analisis Dampak Game Online Terhadap Moral Siswa Kelas VI SDN Tanjung Jati 2 - Qodaria, Rizka Lailatul; Setyawan, Agung; Widayati, Sih (maktab: Jurnal Pendidikan dan Teknologi, 2024)
Increasingly advanced technological developments have brought us the emergence of online games (online games). Currently, online games have penetrated the world of children, as can be seen from the large number of elementary school students who play them. The activity of playing online games certainly has a certain impact on its users. This research aims to analyze the level of addiction to playing online games and describe its impact on student morale in class 6 Tanjung Jati 2. The research results showed that the majority of students showed a tendency towards addiction, where 85% or 17 students admitted to being addicted to playing online games, and 70% or 14 students reported increasing playing duration. The average level of student addiction was recorded as playing every day of the week with the highest percentage reaching 60%, and the average playing time was more than 5 hours per day with a percentage of 55%. The impact of online games on student morale is more negative than positive. The positive impact found was that students gained experience and skills in technology, and were able to enjoy entertainment. However, the negative impacts include increasing emotions that are difficult to control, students who lose track of time, often ask for money for games, tend to be dishonest, lack concern for the environment, health problems, and lazy behavior that causes neglect of other important activities.